1992
DOI: 10.1002/chin.199223314
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Selective Alkali and Alkaline Earth Cation Complexation by Calixarene Amides

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The stability constant of NaL + adducts decreased in the order MeCN > MeOH > DMF, which has been previously observed [7,11,15,35]. All cation hosting reactions were enthalpically controlled and, generally, the complex stabilities were similar to those corresponding to the other tertiary-amide calix [4]arene derivatives [11,[60][61][62], whereby the peak affinity of receptors for sodium was noticed in all explored solvents. The standard complexation entropies were negative in all cases, except for Li + hosting in MeCN.…”
Section: Discussionsupporting
confidence: 77%
“…The stability constant of NaL + adducts decreased in the order MeCN > MeOH > DMF, which has been previously observed [7,11,15,35]. All cation hosting reactions were enthalpically controlled and, generally, the complex stabilities were similar to those corresponding to the other tertiary-amide calix [4]arene derivatives [11,[60][61][62], whereby the peak affinity of receptors for sodium was noticed in all explored solvents. The standard complexation entropies were negative in all cases, except for Li + hosting in MeCN.…”
Section: Discussionsupporting
confidence: 77%
“…In another investigation, it was reported that in the 1,3alternate conformation compound 87a showed significant extraction of K + , Rb + , and Ag + ions 93 due to the participation of the sulfur bridges of the thiacalix [4]arene scaffold in cation binding, whereas the corresponding calix [4]arene analogue extracted Na + , K + , Ca 2+ , and Ba 2+ ions. 94 Further, removal of the tert-butyl groups in compounds 86b,c and 87b,c (Fig. 16) led to a decrease in their extraction ability towards these cations.…”
Section: Thiacalix[4]arene Based Receptors For Cation Recognitionmentioning
confidence: 94%
“…Potentiometric titrations were performed using Ag + electrodes following the procedure described previously . The concentration of the free Ag + cations was measured with a metallic silver electrode (M291 Ag‐9, Radiometer, Copenhagen).…”
Section: Methodsmentioning
confidence: 99%